Efek Teratogenik Sinar X - Arif Faisal, Arif Faisal (Universitas Gadjah Mada, 1981)
The application of X-rays in the medical field has positive and negative effects. The effects of X-ray radiation to the intrauterine embryo and foetus depend on the period of gestation. In the first trimester the embryo may be resorbed and aborted and may also be born with serious defects. In the late trimester radiation may cause less serious defects and it may disturb the function of organs. Many defects involve nerve names and are associated with symptoms of mental retardation.To prevent radiation exposure to embryo and foetus, it is necessary to observe the